Externalising moods and psychological states in a cloud based system to enhance a pet-robot and child's interaction. - Larriba, Ferran.; Raya, Cristóbal.; Angulo, Cecilio.; Albo-Canals, Jordi.; Díaz, Marta.; Boldú, Roger. (2016)
Background: This PATRICIA research project is about using pet robots to reduce pain and anxiety in hospitalized children. The study began 2 years ago and it is believed that the advances made in this project are significant. Patients, parents, nurses, psychologists, and engineers have adopted the Pleo robot, a baby dinosaur robotic pet, which works in different ways to assist children during hospitalization.; Springer Open.